2010
DOI: 10.1111/j.1440-1681.2010.05389.x
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin augments angiotensin II‐induced renal vasoconstriction in kidneys from rats with metabolic syndrome

Abstract: SUMMARY Dipeptidyl peptidase IV (DPPIV) inhibitors enhance renovascular responses to angiotensin II (Ang) in spontaneously hypertensive rats (SHR) but not Wistar-Kyoto rats. Because DPPIV inhibitors are often used in the metabolic syndrome, it is important to determine whether in this setting DPPIV inhibition enhances renovascular responses to Ang. Six-week-old Lean-ZSF1 rats (harbor SHR genes; do not have the metabolic syndrome; n=11) and Obese-ZSF1 rats (harbor SHR genes; express the metabolic syndrome;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 20 publications
0
19
0
1
Order By: Relevance
“…They showed that inhibition of DPP-4 prevents the catabolism of NPY(1-36) and thereby increases the effects of NPY(1-36) released from renal sympathetic nerves on Y1 receptors, thus leading to an enhancement of the renovascular effects of AT-II (85). Along this line, Tofovic et al (84) showed that sitagliptin enhances renovascular responses to AT-II in SHR rats; they also demonstrated that this effect persists in rats with diabetic nephropathy and metabolic syndrome. Kirino et al (86) assessed renal function in F344/DuCrlCrlj rats, a substrain of the inbred Fischer 344 strain lacking DPP-4 enzyme activity.…”
Section: Dpp4-i and The Kidney Experimental Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…They showed that inhibition of DPP-4 prevents the catabolism of NPY(1-36) and thereby increases the effects of NPY(1-36) released from renal sympathetic nerves on Y1 receptors, thus leading to an enhancement of the renovascular effects of AT-II (85). Along this line, Tofovic et al (84) showed that sitagliptin enhances renovascular responses to AT-II in SHR rats; they also demonstrated that this effect persists in rats with diabetic nephropathy and metabolic syndrome. Kirino et al (86) assessed renal function in F344/DuCrlCrlj rats, a substrain of the inbred Fischer 344 strain lacking DPP-4 enzyme activity.…”
Section: Dpp4-i and The Kidney Experimental Studiesmentioning
confidence: 97%
“…The relationship between DPP-4 activity and kidney function is complex, and available studies frequently report conflicting results. Tofovic et al (84) were among the first to underline this complexity, also in the light of the pleiotropic effect of DPP-4. They showed that inhibition of DPP-4 prevents the catabolism of NPY(1-36) and thereby increases the effects of NPY(1-36) released from renal sympathetic nerves on Y1 receptors, thus leading to an enhancement of the renovascular effects of AT-II (85).…”
Section: Dpp4-i and The Kidney Experimental Studiesmentioning
confidence: 99%
“…This finding is consistent with animal data showing that DPP-4 inhibitors reduce BP when given alone but not when coadministered with an ACE inhibitor. 1,6 Additionally, DPP-4 inhibition with vildagliptin 14 potentiates endothelium-dependent vasodilation in response to acetylcholine, whereas others have reported that sitagliptin and alogliptin attenuated endothelial function based on changes in flow-mediated vasodilation in patients with type 2 diabetes mellitus. 15 These vascular findings have been implicated as a potential mechanism for augmented sympathetic activity that could have played a role in the increase in HF hospitalizations in the SAVOR TIMI 53 trial.…”
Section: Discussionmentioning
confidence: 99%
“…5 In addition, experimental data show that DPP-4 inhibition may enhance renal angiotensin II effects in a spontaneously hypertensive rat model. 6 Furthermore, activation of the sympathetic nervous system through substance P may be more likely in the presence of higher dose ACE inhibition and DPP-4 inhibition. 3 For example, the impact of coadministration of a high-dose ACE inhibitor and a DPP-4 inhibitor includes increases in blood pressure (BP) and heart rate in short-term, controlled clinical pharmacology studies.…”
mentioning
confidence: 99%
“…В модели L-NAME-индуцированной (L-NAME -N,ω-нитро-L-аргинина метиловый эфир) гипертензивной нефропатии у крыс ситаглиптин увеличивал содержание eNO-синтазы в по-чечной ткани [46]. Вместе с тем, ситаглиптин усиливал вазоконстриктивное действие ангиотензина II на почеч-ные сосуды в экспериментах на крысах линий Lean-ZSF1 и Obes-ZSF1 со спонтанной АГ [47]. В эксперименте на изолированной почке крыс линии SRH, предрасполо-женных к АГ, описано усиление реноваскулярного эф-фекта ангиотензина II под воздействием ситаглиптина; данный эффект был связан с ингибированием деграда-ции нейропептида Y в симпатических нервах почек [48].…”
Section: ингибиторы дпп-4unclassified